2008
DOI: 10.1158/1078-0432.ccr-08-0373
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Clinical Outcome in Patients Diagnosed with Synchronous Ovarian and Endometrial Cancer

Abstract: Purpose: Patients with synchronous ovarian and endometrial cancers may represent cases of a single primary tumor with metastasis (SPM) or dual primary tumors (DP).The diagnosis given will influence the patient's treatment and prognosis. Currently, a diagnosis of SPM or DP is made using histologic criteria, which are frequently unable to make a definitive diagnosis. Experimental Design: In this study, we used genetic profiling to make a genetic diagnosis of SPM or DP in 90 patients with synchronous ovarian/endo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 29 publications
1
34
0
Order By: Relevance
“…As with linkage analysis for tracking inherited transmission in families, the ability to distinguish between different allelic events at the same marker is a very powerful tool for studying clonality. 6,15 In conclusion, we have used genetic analysis of primary ovarian tumors and their associated metastatic lesions from several patients, to evaluate the mechanisms of clonal evolution and metastatic progression. Our data suggest that most, if not all metastases are clonally related to the primary tumors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As with linkage analysis for tracking inherited transmission in families, the ability to distinguish between different allelic events at the same marker is a very powerful tool for studying clonality. 6,15 In conclusion, we have used genetic analysis of primary ovarian tumors and their associated metastatic lesions from several patients, to evaluate the mechanisms of clonal evolution and metastatic progression. Our data suggest that most, if not all metastases are clonally related to the primary tumors.…”
Section: Discussionmentioning
confidence: 99%
“…We have found previously that there is no correlation between variation in the pattern of LOH and the size of the PCR product. 4,15 The heterozygosity of these markers ranged from 0.71 to 0.90. Markers that failed PCR amplification in tumor samples were excluded from the analysis.…”
Section: Genetic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Eifel et al found that patients with endometrioid cancers at both sites had a better overall prognosis when compared to patients with stage II ovarian disease or stage III endometrial cancer. The GOG study by Ramus et al found that 74 patients with simultaneously detected endometrial and ovarian cancers had an overall good prognosis with a 5-year survival of 85.9 % and 10-year survival of 80.3 % [ 15 ]. Although almost one-third had metastases at operation, only 15 % of the entire study population suffered a recurrence within 5 years of diagnosis.…”
Section: Clinical Presentation and Treatmentmentioning
confidence: 97%
“…MSI is caused by an underlying defect in the mismatch repair (MMR) system. In a study of 90 cases of simultaneous endometrial and ovarian cancers, it was found that histology alone provided a diagnosis in only 61 % of cases, whereas the combination of histology and molecular diagnosis based on LOH at 22 loci and MSI was able to categorize 98 % of cases [ 15 ].…”
Section: Molecular Studiesmentioning
confidence: 99%